PENGARUH PENGETAHUAN PRODUK DAN RELIGIUSITAS TERHADAP KEPUTUSAN PEMBELIAN SCARLETT WHITENING DENGAN SIKAP SEBAGAI VARIABEL MEDIASI - Nanda Irma Rahayu; Ahmad Nizam (FEB Universitas Syiah Kuala, 2023)
This study aims to measure the effect of product knowledge and religiosity on scarlett whithening's purchasing decisions with attitude as a mediating variable. The population used is scarlett whitening product users in the city of Banda Aceh with a sample of 114 respondents. The data collection equipment used in this study was a questionnaire. The sampling technique used was purposive sampling. Path analysis and Sobel test are used as analytical methods to determine the effect of the variables involved. Based on the results of the research analysis, it was found that product knowledge had a positive and significant effect on purchasing decisions. Religiosity has a positive and significant effect on purchasing decisions. Product knowledge has a positive and significant effect on attitudes. Religiosity has a positive and significant effect on attitudes. Attitude has a positive and significant effect on purchasing decisions. And the results of the Sobel test on the indirect effect show that product knowledge has a positive and significant influence on purchasing decisions with attitude as a mediating variable. Religiosity has a positive and significant influence on purchasing decisions with attitude as a mediating variable.